Challenges in Implementing the Makan Bergizi Gratis (MBG) Program in West Bandung Regency: Between Policy Goals and Field Realities - Setiadi, Ade; Muhafidin, Didin; Rohadin (GoAcademica Research & Publishing, 2025)
Makan Bergizi Gratis (MBG) is one of the government’s initiatives to improve school children’s nutrition and reduce stunting rates in Indonesia. However, its implementation in West Bandung Regency still faces various challenges. The occurrence of mass food poisoning among students after consuming MBG meals highlights weak food quality monitoring, limited resources, and suboptimal coordination between schools, food providers, and related agencies. This study aims to analyze the implementation of the MBG program in West Bandung Regency using a descriptive qualitative approach. The findings reveal that the MBG program has not been fully implemented in accordance with the expected standards. The main inhibiting factors include weak monitoring systems, lack of food safety education, and inadequate cross-sectoral collaboration. Therefore, strengthening monitoring mechanisms, enhancing implementers’ capacity, and encouraging community involvement are essential to ensure that the MBG program is safe, healthy, and sustainable.